2018
DOI: 10.3390/rs10060858
|View full text |Cite
|
Sign up to set email alerts
|

Night-Time Light Dynamics during the Iraqi Civil War

Abstract: In this study, we analyzed the night-time light dynamics in Iraq over the period 2012-2017 by using Visible Infrared Imaging Radiometer Suite (VIIRS) monthly composites. The data quality of VIIRS images was improved by repairing the missing data, and the Night-time Light Ratio Indices (NLRIs), derived from urban extent map and night-time light images, were calculated for different provinces and cities. We found that when the Islamic State of Iraq and Syria (ISIS) attacked or occupied a region, the region lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…By inter-calibrating DMSP-OLS and VIIRS monthly composites, the NTL dynamics during January 2011 to January 2017 were analyzed, showing a slight recovery of NTL due to the peace agreement between the Syrian Government and the rebel groups [118]. In addition to the Syrian conflict, VIIRS images have also been applied to analyze the civil wars in Yemen [119] and Iraq [120,121], showing that the time series VIIRS images are able to reflect electricity usage during the war.…”
Section: Conflicts and Disastersmentioning
confidence: 99%
“…By inter-calibrating DMSP-OLS and VIIRS monthly composites, the NTL dynamics during January 2011 to January 2017 were analyzed, showing a slight recovery of NTL due to the peace agreement between the Syrian Government and the rebel groups [118]. In addition to the Syrian conflict, VIIRS images have also been applied to analyze the civil wars in Yemen [119] and Iraq [120,121], showing that the time series VIIRS images are able to reflect electricity usage during the war.…”
Section: Conflicts and Disastersmentioning
confidence: 99%
“…Numerous studies have demonstrated that the range and intensity of NTL are closely correlated to gross regional products (GRP) [6,[15][16][17], size and density of population [17][18][19], urbanization [2,20,21], electricity consumption [1,6,[22][23][24], light pollution [25][26][27], carbon dioxide (CO 2 ) emissions [28,29], and humanitarian disasters, etc. [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Using remote sensing images to extract UBD information is also a fast and effective method to make up for the shortcomings of traditional manual mapping methods. Existing studies on UBD tend to use high-resolution remote sensing satellites for research because they are more accurate [11,28,29], but their shortcomings are also obvious, such as complex building analysis, the cumbersome automated extraction process, and a large number of computations.NTL remote sensing is widely used in macroeconomic and social parameter estimation [30][31][32], urban monitoring [33][34][35][36], great event change [37,38], energy consumption [39,40], ecological environment assessment [41,42], and other fields. Due to the low spatial resolution of NTL images, previous studies focused on macroscopic dimensions, such as national or urban scales.…”
mentioning
confidence: 99%
“…NTL remote sensing is widely used in macroeconomic and social parameter estimation [30][31][32], urban monitoring [33][34][35][36], great event change [37,38], energy consumption [39,40], ecological environment assessment [41,42], and other fields. Due to the low spatial resolution of NTL images, previous studies focused on macroscopic dimensions, such as national or urban scales.…”
mentioning
confidence: 99%